Students’ academic resilience and well-being in Ghana: the mediating effects of grit and motivation - Paul Obeng; Medina Srem-Sai; Francis Arthur; Iddrisu Salifu; Mustapha Amoadu; Edmond Kwesi Agormedah; John Elvis Hagan; Thomas Schack (Discover Education)
Abstract Background Academic resilience is vital in students’ success, but its mechanisms in promoting academic well-being remain underexplored. This study investigated the direct effects of resilience on well-being, grit, and motivation and examined the mediating roles of grit and motivation in these relationships among Senior High School (SHS) students in Ghana. Method A descriptive correlational design was used, sampling 190 SHS students through stratified random sampling. Data were gathered using validated instruments for academic resilience (ARS-30), well-being (SSWQ), grit (AGS), and motivation (MSLQ). Partial Least Squares Structural Equation Modeling (PLS-SEM) analysed relationships and mediation effects, with bootstrapping (10,000 samples) employed for hypothesis testing. Results The analysis confirmed significant direct effects of academic resilience on grit (β = 0.518, p < 0.001), motivation (β = 0.479, p < 0.001), and well-being (β = 0.168, p = 0.022). Grit (β = 0.321, p < 0.001) and motivation (β = 0.356, p < 0.001) were significant predictors of well-being. Mediation analysis showed that grit (β = 0.166, p < 0.001) and motivation (β = 0.170, p < 0.001) partially mediated the relationship between resilience and well-being. Conclusion This study underscores the significant role of academic resilience in enhancing students' well-being, with grit and motivation as key mediators. The findings suggest that fostering resilience, grit, and motivation can improve academic outcomes. Educational institutions should integrate strategies that promote these traits, such as resilience-building programs and mental health support. Policymakers are encouraged to prioritize initiatives that nurture these qualities to enhance students' academic success and well-being.